ANALISA DAYA SAING INDUSTRI PERTEMUAN (MICE) INDONESIA BERBASIS MODEL SEMBILAN FAKTOR CHO - Wahyudi Utomo (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2023)
ABSTRACT : This study aims to determine the structure of industrial competitiveness in the MICE industry. This research is a study to examine the factors that cause the Indonesian MICE industry to survive in the midst of global competition despite various problems and to create a model for the competitiveness structure. However, in recent years the growth of Indonesia's MICE industry has slowed. To understand further why Indonesia's MICE industry has stagnated, an analysis of the competitive structure of the Meetings, Incentives, Conventions, and Exhibitions (MICE) industries is carried out, which is the fastest growing tourism sector and generates large foreign exchange for a country, MICE is able to increase trade and investment. , provide jobs, boost local economies, and promote destinations. The qualitative approach in this study uses a list of questions that serve as guidelines for in-depth interviews with several informants. The selection of informants in this study was based on work experience and had held leadership positions in government, industry and industry associations. The results of a research study on the competitiveness structure of the Indonesian MICE industry showed that there were only two of Cho's nine competitiveness factors which were the driving factors. Indonesia's MICE industry competitiveness, namely: (1) Business Environment and (2) Entrepreneurship. Meanwhile, other factors are still obstacles to increasing the competitiveness of Indonesia's MICE industry. Keywords: Competitiveness, MICE,